Gab2 plays a carcinogenic role in ovarian cancer by regulating CrkII - Yi Yin; Li Zhang; Yong Li; Can Zhang; Aiqin He (BMC, 2023)
Abstract Objective To detect the expression of Growth factor binding protein 2 associated binding protein 2 (Gab2) and CT10 regulator of kinase II (CrkII) in ovarian cancer and analyze their clinical significance. To explore the effects of Gab2 and CrkII on the biological behavior of ovarian cancer cells. To analyze the possible molecular mechanism of Gab2 in the development of ovarian cancer. Methods Immunohistochemistry was used to detect the expression of Gab2 and CrkII in ovarian cancer. Chi square test was used to analyze the correlation between Gab2, CrkII and clinical parameters. Using Cox regression model to evaluate the risk factors affecting the prognosis. To analyze the correlation between Gab2, CrkII and survival rate by Kaplan-Meier. Cell experiments were preformed to explore the effects of Gab2 and CrkII on the biological behavior of cells. The interaction between Gab2 and CrkII was explored by immunoprecipitation. Results Immunohistochemistry revealed that high expression of Gab2 and CrkII in ovarian cancer. Patients with high expression of Gab2 or CrkII had higher International Federation of Gynecology and Obstetrics (FIGO) stage, grade and platinum-resistance recurrence. Multivariate analysis showed that Gab2 and CrkII were independent prognostic factors. Kaplan-Meier curve showed that the higher Gab2 and CrkII were, the poor prognosis the patients had. We observed that the overexpression of Gab2 and CrkII promoted the proliferation, metastasis and reduced chemosensitivity of cells. Conversely, the knockdown of Gab2 and CrkII resulted in the opposite results. In CrkII-knockdown cells, we found that Gab2 mediates biological behavior through CrkII. Conclusions The expression of Gab2 and CrkII increase in ovarian cancer. The higher expression of Gab2 and CrkII predict the poor prognosis of patients. Gab2 and CrkII promote the proliferation and migration and reduce the chemosensitivity of cells. Gab2 regulates the biological behaviors of ovarian cancer cells through CrkII.